APPRAISEMENT OF GATEWAY AND USAGE OF LIBRARY INFORMATION RESOURCES AMONG PUPILS IN OSOGBO LGEA, NIGERIA - Ajibola, Kolawole Sunday (Annals of Spiru Haret University. Economic Series, 2021)
Regarding the vital role of school libraries in the educational system, there are issues around the qualified human resources, adequate facilities, and electricity supply among others. Another challenge is the proper attitudes towards the use of the available library information resources among library users. The trend which is not helpful to national development in any way if not curbed. To find out ways around the emerging attitudes, this study was motivated to investigate the appraisement of gateway and usage of library information resources among pupils in Osogbo Local Government Education Authority (LGEA), Osun State, Nigeria. The intentions of the study were to determine the level of satisfaction of pupils towards school library information resources including human resources, and other facilities; to investigate access and use of school library information resources, to find out the factors that pose problem to pupils in the use of school library and strategies to overcome such challenges. In a descriptive survey, simple random was habituated to select 40 respondents from each of the selected primary schools to make a sample size of 240 respondents in six primary schools purposively selected in the Osogbo Local Government Area of Osun State in Nigeria. The methods of data collection for the study were questionnaires, documentary review, personal observations and interview. Content analysis was espoused for qualitative data. Quantitative data were anatomised by using SPSS. The finding divulged that primary school pupils face many repressions in using the school library since there are no current library information resources but obsolete ones; inadequate of qualified and professional personnel. It was also found that books were the most frequently used library information resources. Furthermore, to effectively use the school’s libraries by the primary school pupils, there is need to address the above-mentioned constraints faced by the pupils in using the school library. The study recommended that provision of fund is necessary to execute all the school library needs. The study further recommended continuous training and retraining for the library human resources.